Effect of reduced osmolality in glucose-based extenders on the post-thaw motility of Mediterranean brown trout (Salmo cettii) spermatozoa - Krasilnikova, Aleksandra; Di Iorio, Michele; Antenucci, Emanuele; Esposito, Stefano; Iaffaldano, Nicolaia; Pšenička, Martin (Frontiers in Marine Science, 2025)
The current study aimed to compare the effects of decreasing osmolality in glucose-based extenders containing methanol alone versus a methanol-ethylene glycol combination on the post-thaw motility of Mediterranean brown trout (Salmo cettii) spermatozoa. Milt was collected from mature males in the Biferno River, Southern Italy, and cryopreserved using a control cryomedium (150 mM glucose with 7.5% methanol) and experimental variants with reduced glucose (100 mM, 50 mM) paired with methanol alone or combined with 2.5% ethylene glycol. Samples were cryopreserved in 0.25 mL straws with a final sperm concentration of 3.0 × 109 spermatozoa/mL, corresponding to 750 × 106 spermatozoa/straw. Sperm motility and kinematic parameters of Mediterranean brown trout were assessed for fresh sperm and post-thaw samples cryopreserved in various cryomedia. Fresh sperm exhibited robust motility (89.0 ± 8.4%) and curvilinear velocity (VCL, 121.2 ± 22.4 µm/s), while the control cryomedium preserved motility at 65.9 ± 12.9% and VCL at 117.6 ± 26.1 µm/s; the experimental 100 mM glucose with 7.5% methanol and 2.5% ethylene glycol treatment yielded comparable motility (65.6 ± 11.6%) but reduced VCL (81.5 ± 16.1 µm/s, p < 0.05). Other treatments showed diminished efficacy, particularly at 50 mM glucose. These findings reveal that a hypotonic extender with methanol-ethylene glycol synergy sustains motility after cryopreservation despite lower glucose levels, demonstrating that the osmotic threshold of extender can be lowered to 100 mOsm/kg without compromising salmonid sperm function. This approach offers a practical tool for conserving S. cettii, supporting broader restoration efforts amid escalating environmental pressures.